Protective effect of Curculigo orchioides in streptozotocin and nicotinamide-induced diabetic neuropathic pain in Wistar rats - Krishan Singla, Randhir Singh (Journal of Applied Pharmaceutical Science, 2020)
Pain, paraesthesia, sensory loss, and associated high morbidity and mortality are typically characterized by diabetic neuropathy (DN). Curculigo orchioides (CO) is a herbal medicine that is rich in flavonoids, glycosides, and polyphenols which are known for potential antioxidant activity. Moreover, the anti-hyperglycemic potential of CO paved the way for pharmacological investigation in the treatment of diabetic complications since the regulation of hyperglycemia is considered as a major factor in the treatment of diabetes. The current study was designed to evaluate the neuroprotective effect of CO extract in DN. DN was induced in rats using streptozotocin (STZ) (65 mg/kg, i.p.) after 15 minutes of nicotinamide (NAD; 230 mg/kg, i.p.). Diabetic rats showed significant mechanical, thermal hyperalgesia, and allodynia. Diabetic rats also showed increased oxidative stress parameters and advanced glycation end products (AGEs) formation. Oral treatment was started on 60th day after STZ–NAD administration and continued for the next 30 days, with different doses (150, 300, and 600 mg/kg) of CO extracts (ethanolic and hydroalcoholic) and standard drug gabapentin (30 mg/kg). The results of the study revealed that both extracts reduced hyperglycemia and inhibited the pain response partially via reduction of oxidative stress and AGEs formation in DN rats. Both the extracts reduced the neuropathic pain in diabetic rats at dose dependent manner.
Keywords: Neuropathic pain, Curculigo orchioides, Streptozotocin, Hyperalgesia, Allodynia.